Our Social Reality in the Covid-19 Pandemic: The Hearing İmpaired - Aydın, Esra (Turkey Health Literacy Journal, 2021)
The Covid-19 outbreak that occured in the city of Wuhan, Hubei province of China in the late of 2019 and has spread in the whole World since 12th March 2020, was declared as a pandemic by the World Health Organization has been a serious threat for the people in terms of phsical, mental psychological and social aspects. After the occurance of Covid-19, measures taken in the health and social areas have led to a number of changes in our way of life. Hearing impaired individuals who experienced difficulties in comminication and access to health care in normal life were among the groups most affected by the pandemic period. In this review, some suggestions have been presented that will reduce the effect of pandemic and challenges that hearing impaired people face with.
Keywords: Pandemic; Covid-19; Hearing İmparied; Health Care Service